Environmental technology adoption: A study on food and beverage industry in Peninsular Malaysia - Abidin, Rahimi; Abdullah, Che Sobry (2010)
The environmental technology is recognized as an important key factor in achieving a better environmental performance of firms and economy.Although the business firms are continuously adopting the technology that reduces the impact of their operations on natural environment, they do so at different rates. There is a wide range of factors that speed up or slow down the adoption of environmental technologies.This paper provides an analysis of factors influencing the adoption of environmental technology among food and beverage firms in Peninsular Malaysia.The main purpose is to determine the relationships of three non-regulatory factors namely technology performances, communication networks and economic factors on environmental technology adoption. This paper begins with an introduction and literature review, followed by the hypotheses statements.To examine these hypotheses, Pearson Correlation analysis was applied. A sample of 76 Malaysian food and beverage firms was used for investigation. The results of the analysis confirmed the hypotheses that there were significant relationships between the three factors and environmental technology adoption.